Propagation of cosh-Airy beams in uniaxial crystals orthogonal to the optical axis. (August 2019) - Zhou, Guoquan; Chen, Ruipin; Chu, Xiuxiang
Highlights: Analytical optical field of a cosh-Airy beam in uniaxial crystals is derived. The centre of gravity, the beam spot size, and the linear momentum are derived. The influence of the uniaxial crystal on the cosh-Airy beam is investigated. The effect of the cosh part on the cosh-Airy beam is also investigated. The propagation properties of the cosh-Airy beam are shown to be abundant. Abstract: Analytical optical field of a cosh-Airy beam propagating in uniaxial crystals orthogonal to the optical axis is presented. Analytical expressions of the centre of gravity, the beam spot size, and the linear momentum for the cosh-Airy beam in uniaxial crystals are also derived, respectively. The propagation properties of a cosh-Airy beam are numerically demonstrated in the uniaxial crystal. The cosh-Airy beam still has the feature of self-acceleration in the two transverse directions. However, the cosh-Airy beam in the y -direction accelerates more slowly than that in the x -direction. The centre of gravity and the beam spot size in the y -direction are always less than those in the x -direction. The influence of the uniaxial crystal on the intensity distribution, the phase distribution, the centre of gravity, the beam spot size, and the linear momentum of a cosh-Airy beam is investigated. The effect of the cosh part on the centre of gravity, the beam spot size, and the linear momentum is also studied in detail. The centre of gravity of the cosh-Airy beam is less than that of the corresponding Airy beam. However, the beam spot size and the linear momentum of the cosh-Airy beam are larger than those of the corresponding Airy beam.